Polycrystalline layered metal oxides containing nanocrystals

Nanocrystalline lithium metal oxide particles with controlled calcination and grain boundary enrichment address the stability and cycling issues of LiNiO2-based cathodes, enhancing discharge capacity and cycle life in lithium-ion batteries.

JP7669311B2Active Publication Date: 2025-04-28CAMX POWER LLC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022042546
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-04-27
Filing Date
2022-03-17
Publication Date
2025-04-28
Estimated Expiration
2037-04-27

AI Technical Summary

Technical Problem

Layered-structured lithium nickel oxide (LiNiO2)-based materials for lithium-ion battery cathodes suffer from poor electrochemical stability and cycling performance due to high impedance increase during charge/discharge cycles, especially with high nickel content, which affects discharge capacity and cycle life.

Method used

The development of polycrystalline lithium metal oxide particles with nanocrystalline structures, having average crystallite sizes of 85 nm or less, and optionally grain boundary enrichments, to reduce impedance increase during cycling, achieved through controlled calcination at temperatures below 700°C and subsequent coating to enhance grain boundary stability.

Benefits of technology

The nanocrystalline particles exhibit improved electrochemical performance with high initial discharge capacity and reduced impedance growth, maintaining capacity and cycle life, achieving discharge capacities over 205 mAh/g at C/20 and lower impedance gradients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669311000008
    Figure 0007669311000008
  • Figure 0007669311000009
    Figure 0007669311000009
  • Figure 0007669311000010
    Figure 0007669311000010
Patent Text Reader

Abstract

Electrochemically active polycrystalline particles are provided that, when incorporated into lithium ion cells, exhibit excellent capacity and improved cycle life. The method includes the step of: providing a plurality of nanocrystals, the plurality of nanocrystals being Li 1+x MO 2+y wherein -0.1≦x≦0.3, -0.3≦y≦0.3, and M comprises 10 atomic percent or more of nickel, wherein M further comprises one or more elements selected from the group consisting of Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Zr, Y, Cr, Mo, Fe, V, Si, Ga, and B, and further comprises an outer coating on a surface of the particle; and the plurality of nanocrystals have an average crystallite size of 85 nanometers or less as measured by x-ray diffraction.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. patent application Ser. No. 62 / 328,447, filed Apr. 27, 2016, the disclosure of which is incorporated herein by reference.

[0002] Field Polycrystalline metal oxide particles, methods for their manufacture, and electrochemical cells or batteries containing same are disclosed.

[0003] background Layered-structured lithium nickel oxide (LiNiO2)-based materials are typically developed for lithium-ion battery cathodes due to their lower cost, higher capacity and higher rate characteristics than the traditional leading LiCoO2 cathode material. However, pure LiNiO2 materials suffer from poor electrochemical stability and cycling performance. To address this, LiNiO2 is formulated with non-nickel elemental additives that stabilize the structure, improving cycling performance but generally at the expense of discharge capacity. As the demand for energy density increases, research is focused on optimizing and reducing these non-nickel additives to obtain the capacity of high-Ni materials while maintaining cycling performance.

[0004] Thus, new materials are needed to address the desire for high capacity materials with long cycle life. The materials and methods for forming such materials provided herein address this need by maintaining high capacity over long cycle life.

[0005] overview The following summary is provided to facilitate understanding of some of the innovative features unique to the present disclosure and is not intended to be a complete description. A complete understanding of the various aspects of the present disclosure will be obtained by taking all of the specification, claims, drawings, and abstract into consideration as a whole.

[0006] It is an object of the present disclosure to provide electrochemically active polycrystalline particles that exhibit superior capacity and improved cycle life when incorporated into a lithium ion cell. The electrochemically active polycrystalline particles include a plurality of nanocrystals, the plurality of nanocrystals being Li 1+x MO 2+y and n is an integer from 0 to 10. Optionally, x is greater than or equal to -0.1 and less than or equal to 0.3. Optionally, y is greater than or equal to -0.3 and less than or equal to 0.3. Optionally, M comprises greater than or equal to 10 atomic percent nickel. The plurality of nanocrystals has an average crystallite size of less than or equal to 85 nanometers as measured by X-ray diffraction (XRD) of the base particle, or an average crystallite size of less than or equal to 105 nanometers as measured by XRD of the coated or grain boundary enriched particles. In some embodiments, M further comprises one or more elements selected from the group consisting of Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Zr, Cr, Mo, Fe, V, Si, Ga, and B.

[0007] Another object is to provide a method of making electrochemically active polycrystalline particles, the method comprising providing a first mixture and calcining the first mixture. The first mixture ("green body") optionally comprises lithium hydroxide or a hydrate thereof and a precursor hydroxide comprising nickel. Calcining the first mixture comprises a maximum temperature of less than 700°C to form a first material comprising a plurality of nanocrystals having a size of 85 nanometers or less. The method optionally further comprises coating the particles and subjecting the particles to a second calcination to densify grain boundaries between the nanocrystals / grains. For the coated particles, the average crystallite size is 105 nm or less.

[0008] The resulting particles and the aforementioned methods achieve the aforementioned objectives by providing materials for producing electrochemical cells having superior capacity and improved cycle life compared to particles having larger crystallites.

[0009] BRIEF DESCRIPTION OF THE DRAWINGS The embodiments depicted in the drawings are illustrative and are not intended to limit the subject matter described in the claims. The following detailed description of illustrative embodiments can be understood when read in conjunction with the following drawings, in which like structure is indicated with like reference numerals and in which:

[0010] Detailed Description The following description of specific embodiments is merely illustrative and is in no way intended to limit the scope of the disclosure, its application, or use, which may of course vary. Materials and methods are described with reference to non-limiting definitions and terms contained herein. These definitions and terms are not intended to limit the scope or practice of the present disclosure, but are presented for illustrative and descriptive purposes only. Although a method or composition is described using a sequence of individual steps or specific materials, it is understood that the steps or materials are interchangeable, and therefore the description of the present invention may include numerous components or steps prepared in numerous ways that are readily apparent to those skilled in the art.

[0011] The present invention will now be described more fully hereinafter with reference to the accompanying drawings, in which various embodiments are shown. The present invention may, however, be embodied in many different forms and should not be construed as limited to the embodiments set forth herein. These embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art. Like reference numerals refer to like elements throughout.

[0012] When an element is referred to as "on" another element, it will be understood that the element can be directly on the other element, or there can be intervening elements between them, whereas when an element is referred to as "directly on" another element, there are no intervening elements present.

[0013] Terms such as "first", "second", "third" and the like are used herein to describe various elements, components, regions, layers and / or sections, but it will be understood that these elements, components, regions, layers and / or sections should not be limited by these terms. These terms are used only to distinguish one element, component, region, layer or section from other elements, components, regions, layers or sections. Thus, unless otherwise stated, a "first element", "component", "region", "layer" or "section" described below can be referred to as a second (or other) element, component, region, layer or section without departing from the teachings of this specification.

[0014] The terms used herein are for the purpose of describing particular embodiments only and are not limiting. As used herein, the singular forms "a," "an," and "this," "it," "the" are intended to include the plural forms, including "at least one," unless the content clearly indicates otherwise. "Or" means "and / or." As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items. It will be further understood that the terms "comprises" and / or "comprising" or "indludes" and / or "including," as used herein, specify the presence of the stated features, regions, integers, steps, operations, elements, components, and / or ingredients, but do not exclude the presence or addition of one or more other features, regions, integers, steps, operations, elements, components, and / or groups thereof. The term "or combinations thereof" means combinations including at least one of the aforementioned elements.

[0015] Unless otherwise stated, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs. Terms as defined in commonly used dictionaries should be interpreted to have a meaning consistent with their meaning in the context of the relevant art and this disclosure, and unless expressly defined herein, should not be interpreted in an ideal or overly formal sense.

[0016] LiMO2-type Ni-based layered materials are dense polycrystalline aggregates of primary crystals. These materials are generally produced using standard solid-state methods at temperatures ranging from 700°C to 900°C starting from various precursor materials. The precursor materials are generally transition metal hydroxides (M(OH)2), lithium precursors (e.g. LiOH or Li2CO3), or inorganic precursors for other dopants (e.g. hydroxides, carbonates, nitrates). During heating of the precursor mixture, polycrystalline LiMO2 is formed with the release of gases such as H2O, CO2 or NO2. At the same time, the primary crystals in the polycrystalline material "sinter" into larger primary crystals. The crystal growth rate during high-temperature synthesis increases significantly with increasing temperature. This effect is expected and has a fundamental thermodynamic explanation, but the inventors have found that it has a detrimental effect on cycle performance.

[0017] During the investigation, the inventors found that larger primary crystals tend to increase the impedance increase rate at the cathode during repeated charge / discharge operations (cycling) of a Li-ion battery. The power supply capacity of a Li-ion battery decreases with increasing impedance of the cathode, which is undesirable for normal battery operation. There are several possible explanations for the higher impedance increase rate with larger crystals. For example, it is known that the surface of the primary crystals is damaged during repeated charge / discharge cycles, causing an increase in the resistance of lithium transport from the grain boundaries into the crystal (i.e., an increase in impedance). For a given battery operating current, the lithium flux or current per unit surface area of ​​the crystal (i.e., surface current density) is higher for larger crystals than for smaller crystals. Even if the resistance increase per unit surface area of ​​the crystal is the same for smaller and larger crystals, the higher surface current density of the larger crystals causes a larger voltage drop, which is manifested as an increase in impedance.

[0018] However, it is difficult to synthetically produce active materials that exhibit a combination of high initial discharge capacity and low impedance increase during cycling. This is especially true when the nickel content of M reaches 90% or more. At such levels of nickel, the crystal growth rates at the synthesis temperatures required to obtain a high degree of crystalline order are extremely high. Primary crystals with sizes significantly exceeding 100 nm, often hundreds of nanometers (nm) or more in size, are already common under known synthesis conditions (as measured by X-ray diffraction).

[0019] Therefore, the present disclosure addresses the aforementioned problems by providing a positive electrode (cathode) active material for Li-ion batteries having nanocrystals to reduce the rate of impedance increase during charge / discharge cycling of the battery. Various methods are provided for achieving high discharge capacity cathode active materials in nickel-containing formulations having average crystallite sizes of 85 nm or less for the base particle material and 105 nm or less for the grain boundary enriched material (both measured by XRD).

[0020] The polycrystalline layered structure lithiated metal oxides having the nanocrystalline structure described herein exhibit improved electrochemical performance and stability. The nanocrystalline compositions prevent degradation of electrochemically cycled Ni-containing polycrystalline LiMO2-based materials while maintaining other desirable end-use article properties, such as the electrochemical capacity of rechargeable lithium-ion cathodes made from such nanocrystalline layered metal oxides, by reducing the rate of impedance increase during electrochemical cycling. Such nanocrystalline compositions can be easily produced by calcining green body formulations containing LiOH and precursor hydroxides or carbonates to a maximum temperature of less than 700°C.

[0021] Thus, compositions, systems, and methods of making polycrystalline layered structure lithiated metal oxides having a nanocrystalline structure and their use in lithium ion secondary cells are provided as a means to achieve high initial discharge capacity and low impedance increase during cycling, thereby solving the aforementioned problem of achieving nanocrystals having an average size of 105 nm or less in high nickel formulations while also having high discharge capacity (e.g., >205 mAh / g at C / 20).

[0022] Throughout this disclosure, reference is made to the crystallite size of nanocrystals within polycrystalline materials. These sizes are determined by XRD, optionally using an automated Shimadzu XRD-6000 diffractometer with a Cu X-ray tube, with powder X-ray diffraction patterns collected by continuous scanning from 2θ=12° to 120° at 0.75° / min. As used herein, the term "nanocrystalline" refers to a crystallite size of 85 nm or less for base materials and 105 nm or less for grain boundary enriched materials with relatively low Co enrichment. It has been found that during the coating process to enrich the grain boundaries with cobalt, the crystallite size can increase slightly due to exposure to high temperatures during calcination. In such circumstances, the crystallite size measured by XRD increases, resulting in materials with measured crystallite sizes of 105 nm or less.

[0023] FIG. 1 shows a schematic diagram (not to scale) of an exemplary polycrystalline layered structure lithiated metal oxide having a nanocrystalline structure. The material includes particles including a plurality of nanocrystals 10, each having a first composition. The particles having a plurality of nanocrystals can be referred to as secondary particles. The particles provided herein are uniquely tailored to have nanocrystals that are much smaller than those considered suitable in the prior art. For example, the particles provided herein include a plurality of nanocrystals having an average crystallite size of 85 nanometers (nm) or less for the base material. The reduced crystallite size provided for reduced impedance increase during cycling improves the performance and cycle life of cells incorporating these particles as a component of the cathode. FIG. 1 further illustrates certain embodiments in which the particles can further include grain boundaries 20 formed from or having a second composition, where, for example, the concentration of cobalt at the grain boundaries is greater than, for example, the concentration of cobalt in the nanocrystals. The grain boundary enriched particles provided herein include a plurality of nanocrystals having an average crystallite size of 105 nanometers (nm). Optionally, as also shown in FIG. 1, a layer 30 can be disposed on the exterior surface of the secondary particles to provide coated secondary particles.

[0024] In some embodiments of the particles provided herein, the first composition has a composition Li 1+x MO 2+yand optionally a cell or battery formed therefrom, wherein -0.1≦x≦0.3 and -0.3≦y≦0.3. In some embodiments, x is -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, x is greater than or equal to -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, -0.04, -0.03, -0.02, -0.01, 0.00, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, or 0.30. In some embodiments, y is -0.3, optionally -0.2, optionally -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, y is -0.30 or greater, -0.29, -0.28, -0.27, -0.26, -0.25, -0.24, -0.23, -0.22, -0.21, -0.20, -0.19, -0.18, -0.17, -0.16, -0.15, -0.14, -0.13, -0.12, -0.11, -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, -0.04, -0. 0.03, -0.02, -0.01, 0.00, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, or 0.3.

[0025] It is understood that in some embodiments, Li need not be exclusively Li, but may be partially substituted with one or more elements selected from the group consisting of Mg, Na, K, and Ca. The one or more elements substituting Li are optionally present at 10 atomic % or less, optionally 5 atomic % or less, optionally 3 atomic % or less, optionally 2 atomic percent or less.

[0026] M provided in the first composition includes Ni. Optionally, the amount of Ni is between 10 atomic percent and 99 atomic percent (at%) of M. Optionally, the Ni content of M is 75 at% or more. Optionally, the Ni content of M is 80 at% or more. Optionally, the Ni content of M is 85 at% or more. Optionally, the Ni content of M is 90 at% or more. Optionally, the Ni content of M is 95 at% or more. Optionally, the Ni content of M is greater than or equal to 75 at%, 76 at%, 77 at%, 78 at%, 79 at%, 80 at%, 81 at%, 82 at%, 83 at%, 84 at%, 85 at%, 86 at%, 87 at%, 88 at%, 89 at%, 90 at%, 91 at%, 92 at%, 93 at%, 94 at%, 95 at%, 96 at%, 98 at%, or 99 at%.

[0027] In some embodiments, M is Ni and one or more additional elements. The additional elements are optionally metals. Optionally, the additional elements may include or be one or more of Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Zr, Y, Cr, Mo, Fe, V, Si, Ga, or B. In certain embodiments, the additional elements may include Mg, Co, Al, or combinations thereof. Optionally, the additional elements may be Mg, Al, V, Ti, B, Zr, or Mn, or combinations thereof. Optionally, the additional elements consist of Mg, Al, V, Ti, B, Zr, or Mn. Optionally, the additional elements consist of Mg, Co, and Al. Optionally, the additional elements consist of Mg, Co, Al, and Zr. Optionally, the additional elements consist of Ca, Co, and Al. In some embodiments, the additional elements are Mn or Mg, or both Mn and Mg.

[0028] The additional element of the first composition may be present in an amount of about 1 at% to about 90 at%, specifically about 5 at% to about 80 at%, more specifically about 10 at% to about 70 at% of the first composition. Optionally, the additional element may be present in an amount of about 1 at% to about 20 at%, specifically about 2 at% to about 18 at%, more specifically about 4 at% to about 16 at% of the first composition. In some illustrative examples, M is about 75 at% to 99 at% Ni, 3 at% to 15 at% Co, 0 at% to 15 at% Mn, and 0 at% to 10 at% of the additional element.

[0029] In polycrystalline materials, each nanocrystal may have any suitable shape, which may be the same or different within each grain. Furthermore, the shape of each nanocrystal may be the same or different in different grains. Due to their crystalline nature, the nanocrystals may be faceted, the nanocrystals may have multiple planes, and the shape of the nanocrystal may approximate a geometric shape. In some embodiments, the nanocrystals may be fused with adjacent nanocrystals whose crystal faces do not coincide. The nanocrystals may have a linear shape, and when viewed in cross section, some or all of the nanocrystals may be linear. The nanocrystals may be square, hexagonal, rectangular, triangular, or combinations thereof.

[0030] In some embodiments relating to base materials that are not enriched in grain boundaries, the average crystallite size of the nanocrystals is about 85 nm or less. Optionally, the average crystallite size of the nanocrystals is about 80 nm or less. Optionally, the average crystallite size of the nanocrystals is about 75 nm or less. Optionally, the average crystallite size of the nanocrystals is about 70 nm or less. Optionally, the average crystallite size of the nanocrystals is about 65 nm or less. Optionally, the average crystallite size of the nanocrystals is about 60 nm or less. Optionally, the average crystallite size of the nanocrystals is about 55 nm or less. Optionally, the average crystallite size of the nanocrystals is about 50 nm or less.

[0031] In some embodiments of base materials that do not have grain boundary enrichment, the nanocrystals have an average crystallite size of 50 nm or more and about 85 nm or less. Optionally, the nanocrystals have an average crystallite size of about 50 nm or more and about 80 nm or less. Optionally, the nanocrystals have an average crystallite size of about 50 nm or more and about 70 nm or less. Optionally, the nanocrystals have an average crystallite size of about 55 nm or more and about 70 nm or less.

[0032] In another embodiment relating to a base material that does not have concentrated grain boundaries, the average crystallite size of the nanocrystals is about 85 nm or less, about 84 nm, about 83 nm, about 82 nm, about 81 nm, about 80 nm, about 79 nm, about 78 nm, about 77 nm, about 76 nm, about 75 nm, about 74 nm, about 73 nm, about 72 nm, about 71 nm, about 70 nm, about 69 nm, about 68 nm, about 67 nm, about 66 nm, about 65 nm, about 64 nm, about 63 nm, about 62 nm, about 61 nm, about 60 nm, about 59 nm, about 58 nm, about 57 nm, about 56 nm, about 55 nm, about 54 nm, about 53 nm, about 52 nm, about 51 nm, or about 50 nm.

[0033] As measured by XRD on the coated material including secondary particles having metal-enriched grain boundaries, such as Co-enriched grain boundaries, the average crystallite size of the nanocrystals is about 105 nm or less. Optionally, the average crystallite size of the nanocrystals is about 100 nm or less. Optionally, the average crystallite size of the nanocrystals is about 95 nm or less. Optionally, the average crystallite size of the nanocrystals is about 90 nm or less. Optionally, the average crystallite size of the nanocrystals is about 85 nm or less. Optionally, the average crystallite size of the nanocrystals is about 80 nm or less. Optionally, the average crystallite size of the nanocrystals is about 75 nm or less. Optionally, the average crystallite size of the nanocrystals is about 70 nm or less.

[0034] In some embodiments of the grain boundary enriched material, the nanocrystals have an average crystallite size of 70 nm or more and about 105 nm or less. Optionally, the nanocrystals have an average crystallite size of about 70 nm or more and about 100 nm or less. Optionally, the nanocrystals have an average crystallite size of about 70 nm or more and about 90 nm or less. Optionally, the nanocrystals have an average crystallite size of about 75 nm or more and about 90 nm or less.

[0035] In another embodiment relating to grain boundary enriched materials, the average crystallite size of the nanocrystals is about 105 nm or less, about 104 nm, about 103 nm, about 102 nm, about 101 nm, about 100 nm, about 99 nm, about 98 nm, about 97 nm, about 96 nm, about 95 nm, about 94 nm, about 93 nm, about 92 nm, about 91 nm, about 90 nm, about 89 nm, about 88 nm, about 87 nm, about 86 nm, about 85 nm, about 84 nm, about 83 nm, about 82 nm, about 81 nm, about 80 nm, about 79 nm, about 78 nm, about 77 nm, about 76 nm, about 75 nm, about 74 nm, about 73 nm, about 72 nm, about 71 nm, or about 70 nm.

[0036] In contrast to the base particles, the grain boundary enriched particles contain Co enrichments at the grain boundaries compared to the nanocrystallites. The presence of Co enrichments can artificially suppress the measurement of nanocrystallite size when measured using XRD, and the increase in the enrichment level of Co at the grain boundaries suppresses the increase in the XRD measurement. For example, the crystallite size of a material in which 6 at% Co (relative to the metal content of the base material) is added to the coating to create a grain boundary enriched material (6 at% Co enrichment) is smaller than the crystallite size of a material with 4 at% Co enrichment. Thus, for coated particles, the measurement of nanocrystallite size is optionally at a particular Co enrichment level. In some embodiments, the nanocrystallite size at 4 at% Co enrichment is 105 nm or less or other levels as described in the paragraph above. Optionally, at 6 at% Co enrichment at the grain boundaries, the nanocrystallite size is 80 nm or less or other values ​​less than 80 nm as otherwise described herein.

[0037] In some embodiments, the grain boundaries are enriched with up to 4 at.% Co and the average crystallite size of the nanocrystals is about 105 nm or less, about 104 nm, about 103 nm, about 102 nm, about 101 nm, about 100 nm, about 99 nm, about 98 nm, about 97 nm, about 96 nm, about 95 nm, about 94 nm, about 93 nm, about 92 nm, about 91 nm, about 90 nm, about 89 nm, about 88 nm, about 87 nm, about 86 nm, about 85 nm, about 84 nm, about 83 nm, about 82 nm, about 81 nm, about 80 nm, about 79 nm, about 78 nm, about 77 nm, about 76 nm, about 75 nm, about 74 nm, about 73 nm, about 72 nm, about 71 nm, or about 70 nm.

[0038] In some embodiments, the grain boundaries are enriched with about 6 at.% cobalt and the average crystallite size of the nanocrystals is about 82 nm or less, about 81 nm, about 80 nm, about 79 nm, about 78 nm, about 77 nm, about 76 nm, about 75 nm, about 74 nm, about 73 nm, about 72 nm, about 71 nm, about 70 nm, about 69 nm, about 68 nm, about 67 nm, about 66 nm, about 65 nm, about 64 nm, about 63 nm, about 62 nm, about 61 nm, about 60 nm, about 59 nm, about 58 nm, about 57 nm, about 56 nm, about 55 nm, about 54 nm, about 53 nm, about 52 nm, about 51 nm, or about 50 nm.

[0039] In some embodiments, the grain boundaries are enriched with 1 at% Co, 2 at% Co, 3 at% Co, 4 at% Co, 5 at% Co, 6 at% Co, 7 at% Co, 8 at% Co, 9 at% Co, 10 at% Co.

[0040] One additional benefit of the particles provided herein according to some embodiments is the increased atomic lattice alignment of nanocrystals in the material. The combination of nanocrystals and improved structural alignment can result in further improved cycle life and reduced impedance increase during cycling for cells incorporating such particles as a component of the cathode. The alignment of nanocrystals allows for the formation of Ni occupying Li sites in the LiNiO2R-3m layered crystal structure. 2+ This can be obtained by measuring the relative abundance of the Ni ions and the relative z-positions of the oxygen atoms.2+ Li can occupy Li sites, can scatter X-rays, and has a relatively large electron density. + It is noted that the above parameters are intended to represent any element considered to be heavier than 3.5 at% Ni (e.g., Ca, Mg, Ni, Co, Al, etc.). 2+ It is believed that the value, together with the crystallite size, has a suitable magnitude to result in improved electrochemical performance of the material. By preparing the grain boundary enriched particles provided herein, Ni at the Li site of the crystal structure can be obtained. 2+ It has been found that average crystallite sizes of 105 nm or less can be formed while still maintaining a relative amount of Ni of 3.5 at% or less. In some embodiments of the grains, with or without enriched grain boundaries, the relative Ni at the Li sites of the crystal structure is 2+ is 3.4 at% Ni or less, optionally 3.3 at% Ni, optionally 3.2 at% Ni, optionally 3.1 at% Ni, optionally 3.0 at% Ni, optionally 2.9 at% Ni, optionally 2.8 at% Ni, optionally 2.7 at% Ni, optionally 2.6 at% Ni, optionally 2.5 at% Ni, optionally 2.4 at% Ni, optionally 2.3 at% Ni, optionally 2.2 at% Ni, optionally 2.1 at% Ni, optionally 2.0 at% Ni, optionally 1.9 at% Ni, optionally 1.8 at% Ni, optionally 1.7 at% Ni, optionally 1.6 at% Ni, optionally 1.5 at% Ni, optionally 1.4 at% Ni. In some embodiments, after the first firing provided herein, the Ni at the Li site of the crystal structure is 2+ The relative amount is up to 1.6 at% Ni, optionally 1.4 at% Ni to 1.6 at% Ni, or any value or range therebetween.

[0041] In certain embodiments, the grains have enriched grain boundaries, optionally Co-enriched grain boundaries where the atomic percentage of Co at the grain boundaries is higher than the atomic percentage of Co in the nanocrystals. Referring again to the exemplary diagram of FIG. 1, the grain boundaries 41, 42 are between adjacent nanocrystals / grains 40, on the surfaces of the nanocrystals / grains 40, and have a second composition. The second composition may be as described in U.S. Pat. Nos. 9,391,317 and 9,209,455 and may be formed substantially as described therein. The second composition may optionally have a layered α-NaFeO2 type structure, a cubic structure, or a combination thereof. As described above, the concentration of cobalt at the grain boundaries may be greater than the concentration of cobalt in the nanocrystals. Particular mention is made of embodiments in which the grain boundaries have a layered α-NaFeO2 type structure.

[0042] The second composition at the grain boundary is optionally of composition Li 1+x MO 2+ywhere -0.9≦x≦0.3 and -0.3≦y≦0.3. In some embodiments, x is -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, x is greater than or equal to -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, -0.04, -0.03, -0.02, -0.01, 0.00, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, or 0.30. In some embodiments, y is -0.3, optionally -0.2, optionally -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, y is -0.30 or greater, -0.29, -0.28, -0.27, -0.26, -0.25, -0.24, -0.23, -0.22, -0.21, -0.20, -0.19, -0.18, -0.17, -0.16, -0.15, -0.14, -0.13, -0.12, -0.11, -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, -0.04, -0. 0.03, -0.02, -0.01, 0.00, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, or 0.3.

[0043] M provided in the second composition comprises Ni. Optionally, the amount of Ni is between 10 atomic percent and 99 atomic percent (at%) of M. Optionally, the Ni content of M is 75 at% or more. Optionally, the Ni content of M is 80 at% or more. Optionally, the Ni content of M is 85 at% or more. Optionally, the Ni content of M is 90 at% or more. Optionally, the Ni content of M is 95 at% or more. Optionally, the Ni content of M is greater than or equal to 75 at%, 76 at%, 77 at%, 78 at%, 79 at%, 80 at%, 81 at%, 82 at%, 83 at%, 84 at%, 85 at%, 86 at%, 87 at%, 88 at%, 89 at%, 90 at%, 91 at%, 92 at%, 93 at%, 94 at%, 95 at%, 96 at%, 98 at%, or 99 at%.

[0044] In some embodiments, M in the second composition is one or more Ni-substituting elements. The Ni-substituting elements are optionally metals. Optionally, the substituting elements may include, or be one or more of, Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Zr, Y, Cr, Mo, Fe, V, Si, Ga, or B. In certain embodiments, the substituting elements may include Mg, Co, Al, or combinations thereof.

[0045] The substitution element of the second composition may be present in an amount of about 1 at% to about 90 at%, specifically about 5 at% to about 80 at%, more specifically about 10 at% to about 70 at% of the first composition. Optionally, the additional element may be present in an amount of about 1 at% to about 20 at%, specifically about 2 at% to about 18 at%, more specifically about 4 at% to about 16 at% of the first composition.

[0046] The shape of the grain boundary is determined by the shape of the crystal grain, which may represent one or more fused nanocrystals adjacent to the grain boundary. The shape of the grain boundary may approximate a geometric shape. The grain boundary may have a linear shape, and when viewed in cross section, the grain boundary may be linear. The grain boundary may be square, hexagonal, rectangular, triangular, or a combination thereof.

[0047] The direction of the grain boundary surface corresponds to the direction of the adjacent nanocrystal surface. Also, as shown in FIG. 1, the grain boundary surface and the nanocrystal surface may have any of a variety of orientations with respect to the outer surface of the grain. Thus, the direction of the nanocrystal surface and the grain boundary surface may be parallel and different from the direction of the surface closest to the exterior of the secondary particle. In some embodiments, the direction of the tangent of the surface closest to the exterior of the grain is different from the direction of the grain boundary surface and the direction of the surface of the adjacent grain.

[0048] As also shown in FIG. 1, the grain boundaries may intersect to form an angle between them. In some embodiments, a first grain boundary 41 and a second grain boundary 42 are disposed on adjacent faces of the nanocrystal / grain 40. The first grain boundary 41 and the second grain boundary 42 intersect at an angle E. The angle E can be determined by the shape of the nanocrystal on which the first grain boundary 41 and the second grain boundary 42 are disposed. In general, the shape of the nanocrystal is influenced by the crystal structure of the nanocrystal. Without wishing to be bound by theory, it is understood that the angle between the first grain boundary 41 and the second grain boundary 42 is influenced by the crystal structure of the first composition, since the crystal structure of the first composition dictates the shape of the nanocrystal. The first grain boundary 41 and the second grain boundary 42 may intersect at any angle, specifically, at an angle between about 10 degrees and about 170 degrees, specifically, between about 20 degrees and about 160 degrees, and more specifically, between about 30 degrees and about 150 degrees, so long as the angle is consistent with the crystal structure of the first composition optionally having a layered α-NaFeO2 type structure.

[0049] The particles can be prepared by synthesizing a green body from at least two components, optionally in powder form. The at least two components can include micronized (or non-micronized) lithium hydroxide or its hydrates and a precursor hydroxide including nickel and one or more other elements. It is understood that the final overall composition (not necessarily in distribution) of the elements in the final particles can be adjusted by increasing or decreasing the relative amounts of the precursor materials in the formation of the green body. In some embodiments, the lithium hydroxide or its hydrates is micronized. The two or more powders forming the green body can be combined and shaken in a paint shaker to thoroughly mix the precursors. The green body is then calcined to a maximum temperature in a regulated air atmosphere, so that water and CO2 are minimized. Calcination is optionally performed according to a heating curve to provide the desired average crystallite size. The calcined product can then be processed to form a flowable powder.

[0050] In some embodiments, the precursor hydroxide may be a mixed metal hydroxide. In some embodiments, the mixed metal hydroxide has a metal composition of Ni, Co, and Mg. Optionally, the mixed metal hydroxide includes 80 at% to 100 at% Ni, 0 at% to 15 at% Co, and 0 at% to 5 at% Mg as metal components. Optionally, the metals of the mixed metal hydroxide are 92 at% Ni and 8 at% Co. Optionally, the metals of the mixed metal hydroxide are 90 at% Ni, 8 at% Co, and 2 at% Mg. Optionally, the metals of the mixed metal hydroxide are 89 at% Ni, 8 at% Co, and 3 at% Mg. Optionally, the metals of the mixed metal hydroxide are 91 at% Ni, 8 at% Co, and 1 at% Mg. Optionally, the metal of the mixed metal hydroxide is 100 at% Ni. For example, the precursor hydroxide may be manufactured by a precursor supplier such as Hunan Brunp Recycling Technology Co. Ltd. using standard methods for preparing nickel hydroxide-based materials.

[0051] It has been found that by reducing the maximum temperature of the first firing, particulate materials having relatively small crystals (i.e., nanocrystals) can be produced. Thus, in the first firing, the maximum temperature can be less than 700°C. Optionally, the maximum temperature can be about 680°C or less. Optionally, the maximum temperature can be about 660°C or less. Optionally, the maximum temperature can be about 640°C or less. In yet another embodiment, the maximum temperature can be less than about 700°C, about 695°C, about 690°C, about 685°C, about 680°C, about 675°C, about 670°C, about 665°C, about 660°C, about 655°C, about 650°C, about 645°C, or about 640°C. Optionally, the dwell time at the maximum temperature is less than 10 hours. Optionally, the dwell time at maximum temperature is 8 hours or less; optionally 7 hours or less; optionally 6 hours or less; optionally 5 hours or less; optionally 4 hours or less; optionally 3 hours or less; optionally 2 hours or less.

[0052] In some embodiments, it has been found that lowering the temperature below the minimum temperature reduces the observed electrochemical improvement. Thus, for the first firing, the maximum temperature in some embodiments is at least about 640°C, optionally about 645°C, and optionally about 650°C. In some embodiments, a maximum temperature must be reached, optionally about 640°C to about 695°C, optionally about 645°C to about 695°C, optionally about 650°C to about 695°C, optionally about 655°C to about 695°C, optionally about 645°C to about 680°C, optionally about 650°C to about 680°C, optionally about 655°C to about 680°C, and optionally about 660°C to about 680°C.

[0053] In some embodiments, the heating curve of the first firing process follows a two-time ramp / dwell process followed by natural cooling to about 130° C. and then processing the fired material. In an exemplary embodiment, the first ramp / dwell may be performed from ambient temperature (e.g., about 25° C.) to 450° C. at a rate of 5° C. per minute and held at 450° C. for 2 hours. Then, the second ramp / dwell may be performed from 450° C. to the maximum temperature at a rate of 2° C. per minute and held at the maximum temperature for 6 hours.

[0054] After calcination, further processing may include crushing the calcined material with a mortar and pestle to allow the resulting powder to pass through a desired sieve, optionally a #35 sieve. This powder is optionally ball milled in a 1 gallon jar with 2 cm drum YSZ media, optionally for 5 minutes, or a suitable time such that the material can optionally pass through a #270 sieve.

[0055] In some embodiments, the milled product may be optionally coated in such a way that enriched grain boundaries are obtained after the second firing. Coating methods for enriching grain boundaries within primary particles may be performed using methods or compositions exemplified in US Pat. Nos. 9,391,317 and 9,209,455. The coating may be optionally applied by suspending the milled product in an aqueous slurry containing enrichment elements, optionally cobalt, and lithium nitrate, optionally at a temperature of 60° C. In this case, the slurry may be spray-dried to form a flowable powder, which is then optionally subjected to a second firing using a heating curve that follows a two-step ramp / dwell process. The first two-step ramp / dwell temperature profile may be performed from ambient temperature (about 25° C.) to 450° C. at a rate of 5° C. per minute, with a hold at 450° C. for 1 hour. A second ramp / dwell may then be performed at a rate of 2° C. per minute from 450° C. to the maximum temperature, holding at this maximum temperature for 2 hours. In some embodiments, the maximum temperature is about 700° C. In other embodiments, the maximum temperature is about 725° C.

[0056] By combining a first firing using the maximum temperature as described above and a coating by a second firing also as described above, it is possible to obtain a Ni alloy containing 3.5 at% or less of Ni while at the same time maintaining an average crystallite size of 105 nm or less (measured by XRD). 2+ It has been found that it is possible to maintain the same continuous orientation of the material comprising the composition Li. It has been found that such a combination results in a reduction in impedance growth which significantly improves the electrochemical performance of the material, in addition to the cycle life. Thus, in some embodiments, the particles are of the composition Li 1+x MO 2+yIt is understood that the nanocrystals include a plurality of nanocrystals having a first composition comprising a polycrystalline layered structure lithiated metal oxide defined by the formula: where -0.1≦x≦0.3 and -0.3≦y≦0.3. In some embodiments, x is -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, x is greater than or equal to -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, -0.04, -0.03, -0.02, -0.01, 0.00, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, or 0.30. In some embodiments, y is -0.3, optionally -0.2, optionally -0.1, optionally 0, optionally 0.1, optionally 0.2, or optionally 0.3. Optionally, y is -0.30 or greater, -0.29, -0.28, -0.27, -0.26, -0.25, -0.24, -0.23, -0.22, -0.21, -0.20, -0.19, -0.18, -0.17, -0.16, -0.15, -0.14, -0.13, -0.12, -0.11, -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, -0.04, -0. 03, -0.02, -0.01, 0.00, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, or 0.3. The nanocrystals have an amount of Ni in the M element of 10 atomic percent to 99 atomic percent (at%) of the particle. Optionally, the Ni content of M is 75 at% or more. Optionally, the Ni content of M is 80 at% or more. Optionally, the Ni content of M is 85 at% or more.Optionally, the Ni content of M is 90 at% or more.Optionally, the Ni content of M is 95 at% or more.Optionally, the Ni content of M is 75 at% or more, 76 at%, 77 at%, 78 at%, 79 at%, 80 at%, 81 at%, 82 at%, 83 at%, 84 at%, 85 at%, 86 at%, 87 at%, 88 at%, 89 at%, 90 at%, 91 at%, 92 at%, 93 at%, 94 at%, 95 at%, 96 at%, 98 at%, or 99 at%. The M component may include one or more additional elements. The additional element is optionally a metal. Optionally, the additional element may include or be one or more of Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Zr, Y, Cr, Mo, Fe, V, Si, Ga, or B. In certain embodiments, the additional element may include Mg, Co, Al, or a combination thereof. Optionally, the additional element may be Mg, Al, V, Ti, B, Zr, or Mn, or a combination thereof. Optionally, the additional element consists of Mg, Al, V, Ti, B, Zr, or Mn. In some embodiments, the additional element is Mn or Mg, or both Mn and Mg. The additional element of the first composition may be present in an amount of about 1 at% to about 90 at%, specifically about 5 at% to about 80 at%, more specifically about 10 at% to about 70 at% of the first composition. Optionally, the additional element may be present in an amount of about 1 at% to about 20 at%, specifically about 2 at% to about 18 at%, more specifically about 4 at% to about 16 at% of the first composition. In some illustrative examples, M is about 75 at% to 99 at% Ni, 3 at% to 15 at% Co, 0 at% to 15 at% Mn, and 0 at% to 10 at% additional element. Additionally, the average crystallite size of the nanocrystals (as measured by the X-ray diffraction method described above) is about 105 nm or less. Optionally, the average crystallite size of the nanocrystals is about 100 nm or less. Optionally, the average crystallite size of the nanocrystals is about 95 nm or less. Optionally, the average crystallite size of the nanocrystals is about 90 nm or less. Optionally, the average crystallite size of the nanocrystals is about 85 nm or less. Optionally, the average crystallite size of the nanocrystals is about 80 nm or less. Optionally, the average crystallite size of the nanocrystals is about 75 nm or less. Optionally, the average crystallite size of the nanocrystals is about 70 nm or less.In some embodiments, the nanocrystals have an average crystallite size of 70 nm or more and about 105 nm or less. Optionally, the nanocrystals have an average crystallite size of about 70 nm or more and about 100 nm or less. Optionally, the nanocrystals have an average crystallite size of about 70 nm or more and about 105 nm or less. Optionally, the nanocrystals have an average crystallite size of about 75 nm or more and about 100 nm or less. In another embodiment, the nanocrystals have an average crystallite size of about 105 nm or less, about 104 nm, about 103 nm, about 102 nm, about 101 nm, about 100 nm, about 99 nm, about 98 nm, about 97 nm, about 96 nm, about 95 nm, about 94 nm, about 93 nm, about 92 nm, about 91 nm, about 90 nm, about 89 nm, about 88 nm, about 87 nm, about 86 nm, about 85 nm, about 84 nm, about 83 nm, about 82 nm, about 81 nm, about 80 nm, about 79 nm, about 78 nm, about 77 nm, about 76 nm, about 75 nm, about 74 nm, about 73 nm, about 72 nm, about 71 nm, or about 70 nm.

[0057] Optionally, the particles contain Ni occupying Li sites in the LiNiO2R-3m layered crystal structure. 2+ The nanocrystals further have an atomic lattice arrangement as indicated by the relative amounts of ions, wherein Ni 2+ The value is 3.5% or less, optionally less than 3.2 at% Ni, optionally 2.5% or less. The atomic % of Ni in the M element is optionally 75 at% to 99 at%, optionally 80 at% to 95 at%.

[0058] Optionally, an outer layer, such as a passivation layer or protective layer, illustrated at 30 in FIG. 1, may be disposed on the outer surface of the particle. This outer layer may completely or partially cover the secondary particle. This layer may be amorphous or crystalline. This layer may include an oxide, phosphate, pyrophosphate, fluorophosphate, carbonate, fluoride, oxyfluoride, or combination thereof of an element such as Zr, Al, Ti, Al, B, Li, or Si, or a combination thereof. In some embodiments, the outer layer includes a borate, an aluminate, a silicate, a fluoroaluminate, or a combination thereof. Optionally, the outer layer includes a carbonate. Optionally, the outer layer includes ZrO2, Al2O3, TiO2, AlPO4, AlF3, B2O3, SiO2, Li2O, Li2CO3, or a combination thereof. Optionally, the outer layer includes or is AlPO4 or Li2CO3. This layer can be deposited by any method or technique that does not adversely affect the desired properties of the particles. Exemplary methods include, for example, spray coating and dip coating.

[0059] Also provided is an electrode that includes the particles described herein as the only electrochemically active material component or as the only electrochemically active material. The particles provided herein are optionally included as the active component of a cathode. Optionally, the cathode includes the particles disclosed above as an active material and further includes a conductive agent and / or a binder. The conductive agent includes any conductive agent that provides suitable properties and may be amorphous, crystalline, or a combination thereof. The conductive agent may include carbon black, such as acetylene black or lamp black, mesocarbon, graphite, carbon fiber, carbon nanotubes, such as single-walled carbon nanotubes or multi-walled carbon nanotubes, or a combination thereof. The binder may be any binder that provides suitable properties and may include, for example, polyvinylidene fluoride, copolymers of polyvinylidene fluoride and hexafluoropropylene, poly(vinyl acetate), vinyl butyral-vinyl alcohol-vinyl acetate copolymer, methyl methacrylate-ethyl acrylate copolymer, acrylonitrile, vinyl chloride-vinyl acetate copolymer, polyvinyl alcohol, 1-vinylpyrrolidone-vinyl acetate copolymer, cellulose acetate, polyvinylpyrrolidone, polyacrylates, polymethacrylates, polyolefins, polyurethanes, polyvinyl ethers, acrylonitrile-butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene-styrene, sulfonated styrene / ethylene-butylene / styrene triblock polymers, polyethylene oxide, or combinations thereof.

[0060] The cathode can be made by combining the particles, conductive agent, and binder described herein in a suitable ratio, for example, about 80% to about 98% by weight of the particles, about 2% to about 20% by weight of the conductive agent, and about 2% to about 10% by weight of the binder, based on the total weight of the particles, conductive agent, and binder combined. The particles, conductive agent, and binder can be suspended in a suitable solvent, such as N-methylpyrrolidinone, and placed on a suitable substrate, such as aluminum foil, and allowed to dry in air. It is noted that the substrate and solvent are shown for illustrative purposes only. Other suitable substrates and solvents can be used or combined to form the cathode.

[0061] In some embodiments, a cathode comprising a polycrystalline material having an average crystallite size of nanocrystals of about 85 nm or less or 105 nm or less, depending on the presence or absence of enriched grain boundaries, can exhibit an electrochemical discharge capacity of greater than 205 mAh / g at a C / 20 rate when the electrode is charged to 4.3 V vs. L metal and discharged to 3.0 V. In yet another embodiment, the cathode can exhibit an electrochemical discharge capacity of greater than 200 mAh / g at a C / 20 rate when the electrode is charged to 4.3 V vs. L metal and discharged to 3.0 V. In yet another embodiment, the cathode can exhibit an electrochemical discharge capacity of greater than 190 mAh / g at a C / 20 rate when the electrode is charged to 4.3 V vs. L metal and discharged to 3.0 V. In yet another embodiment, the cathode can exhibit an electrochemical discharge capacity of greater than 180 mAh / g at a C / 20 rate when the electrode is charged to 4.3 V vs. L metal and discharged to 3.0 V. In yet another embodiment, the cathode can exhibit an electrochemical discharge capacity of greater than 175 mAh / g at a C / 20 rate when the electrode is charged to 4.3 V vs. L metal and discharged to 3.0 V. In yet another embodiment, the cathode can exhibit an electrochemical discharge capacity of greater than 170 mAh / g at a C / 20 rate when the electrode is charged to 4.3 V vs. L metal and discharged to 3.0 V.

[0062] The cathode described above optionally shows a significant reduction in impedance increase when cycled in a 2025 coin cell with a lithium foil anode, a polyolefin separator, and an electrolyte of 1M LiPF6 in 1 / 1 / 1 (by volume) EC / DMC / EMC with 1% by weight VC. One measure of impedance increase is shown by charging the cell at a 1C rate to 4.2V (CCCV) and discharging the cell to 2.7V. The time spent at a constant voltage during this characterization step can be used as a measurement of impedance. Impedance measurements plotted against cycle number result in a curve with a given slope. The impedance slope is lower when the active particle material has a crystallite size or size as described herein compared to particles with larger crystallite sizes (e.g., greater than 85 nm). In some embodiments, the impedance gradient is 0.025 or less, optionally 0.024 or less, optionally 0.023 or less, optionally 0.022 or less, optionally 0.021 or less, optionally 0.020 or less, optionally 0.019 or less, optionally 0.018 or less, optionally 0.017 or less, optionally 0.016 or less, optionally 0.015 or less.

[0063] Also disclosed is a battery comprising the cathode. The battery may be, for example, a lithium ion battery, a lithium polymer battery, or a lithium battery. The battery may comprise a cathode, an anode, and a separator disposed between the cathode and the anode. The separator may be a microporous membrane, may comprise a porous coating comprising polypropylene, polyethylene, or a combination thereof, or may be a woven or non-woven material, for example, a glass fiber mat. The anode may comprise a coating on a current collector. The coating may comprise, for example, a suitable carbon, for example, graphite, coke, hard carbon, or mesocarbon, for example, mesocarbon microbeads. The current collector may be, for example, a copper foil.

[0064] The battery also includes an electrolyte that may contact the positive electrode (cathode), the negative electrode (anode), and the separator. The electrolyte may include an organic solvent and a lithium salt. The organic solvent may be a linear or cyclic carbonate. Exemplary organic solvents include ethylene carbonate, propylene carbonate, butylene carbonate, trifluoropropylene carbonate, gamma-butyrolactone, sulfolane, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 3-methyl-1,3-dioxolane, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, propane sultone, or combinations thereof. In another embodiment, the electrolyte is a polymer electrolyte.

[0065] Representative lithium salts useful in the electrolyte include, but are not limited to, LiPF6, LiBF4, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiN(SO2C2F5)2, LiSbF6, LiC(CF3SO2)3, LiC4F9SO3, and LiAlCl4. The lithium salt can be dissolved in an organic solvent. Combinations comprising at least one of the foregoing lithium salts can be used. The concentration of the lithium salt can be from 0.1 M to 2.0 M in the electrolyte.

[0066] The cells may have any suitable configuration or shape and may be circular or prismatic.

[0067] Various aspects of the present disclosure are illustrated by the following non-limiting examples. These examples are for illustrative purposes and are not intended to limit the practice of the present invention. It will be understood that modifications and variations can be made without departing from the spirit and scope of the present invention. [Brief description of the drawings]

[0068] [Figure 1] FIG. 1 is a schematic cross-sectional perspective view of an electrochemically active polycrystalline particle according to one or more embodiments described herein. [Diagram 2]1 is a graph showing the discharge performance of cathode materials having large crystallite size (109 nm) and small crystallite size (78 nm) at 100-200 cycles in a dual cell according to one or more embodiments described herein. [Diagram 3] 4 is a graph showing impedance values ​​for dual cells including cathode materials having large and small crystallites corresponding to the discharge performance data shown in FIG. 3 in accordance with one or more embodiments described herein. [Figure 4] Graph showing impedance values ​​at 100-200 cycles for dual cells including cathode materials having a range of crystallite sizes formed by calcination at temperatures up to 700° C. in accordance with one or more embodiments described herein.

[0069] Working Example The average crystallite size of the nanocrystals can be determined using powder X-ray diffraction patterns collected by continuous scanning from 2θ = 12° to 120° at 0.75° / min using an automated Shimadzu XRD-6000 diffractometer equipped with a Cu X-ray tube. Atomic structure and crystallite size analysis can be performed using Rietveld techniques implemented in the MDI Jade 7 program or other equivalent programs. The procedure for atomic structure refinement will be apparent to one skilled in the art. Such refinement can be used to determine the a- and c-lattice parameters of the LiNiO2R-3m layered crystal structure and the Ni occupying the Li sites. 2+ The relative amounts of ions and the relative z-positions of oxygen atoms can be obtained. Third order polynomial background curves and Pseudo-Voigt profile shape functions can be used for peak fitting. Peak broadening can be fitted with MDI Jade for both crystallite size and strain, or only for crystallite size. Crystallite size fitting only (without strain) is used to measure the average primary crystallite size of materials synthesized under different reaction conditions. FWHM calibration curves using the instrument can be obtained by profile fitting diffraction patterns of calibration standards such as NIST SRM 640 Si or SRM 660 LiB6 powders.

[0070] Example 1: Two samples of polycrystalline 2D α-NaFeO2-type layered structure particles with different crystallite sizes Two electrochemically active polycrystalline 2D α-NaFeO2-type layered structure particles with different crystallite sizes of high nickel were prepared as cathode materials. The two samples of polycrystalline 2D α-NaFeO2-type layered structure prepared had the bulk composition Li (0.98) Mg (0.02) Ni (0.881) Co (0.115) Al (0.004) O (2.0) One sample was produced by firing the green body at 700°C and a second firing at 680°C. Two materials were produced from the same green body formulation containing 80.21 g of finely divided LiOH and 288.2 g of precursor hydroxide, which contained an atomically mixed combination of 90.2 at% Ni, 7.8 at% Co, and 2.0 at% Mg.

[0071] Two portions of the green blend were then fired with different heating curves in a flow of CO2-free dry air. The "high temperature", used to produce "large crystallites", was ramped from 25°C to 450°C at 5°C / min with a 2 hour soak time, followed by a second ramp at 2°C / min to a maximum temperature of 700°C and a 6 hour soak time. The "low temperature", used to produce "small crystallite size" (meaning nanocrystals), was ramped from 25°C to 450°C at 5°C / min with a 2 hour soak time, followed by a second ramp at 2°C / min to a maximum temperature of 680°C and a 6 hour soak time.

[0072] Each material was then naturally cooled to 100° C. Each calcined material was first ground in a mortar and pestle, then crushed in a ball mill. The “large crystallite” product was milled for 10 minutes, while the “small crystallite size” material was milled for 5 minutes.

[0073] The properties of the two materials are summarized in Table 1. These two materials were subjected to a series of tests to determine the average oxidation state, residual lithium hydroxide, and ionic mixing in the layered crystallites. The synthesized materials were virtually identical to the typical metrics commonly used to characterize cathode powders (oxidation state, residual lithium hydroxide, and cation mixing). The only significant difference was the average crystallites.

[0074] [Table 1]

[0075] Prior to forming the electrodes, the synthesized powders were coated with a mixture of cobalt and aluminum using the same method to a sufficient extent to produce the aforementioned formulations to enrich the grain boundaries. After coating both materials, the materials were subjected to another heat treatment under flowing CO2-free dry air. The heating curve used for this treatment was ramped from 25°C to 450°C at 5°C / min with a soak time of 1 hour, followed by a second ramp at 2°C / min to 700°C and a soak time of 2 hours. The materials were then naturally cooled to 100°C and ground in a ball mill for 5 minutes. The obtained parameters of the grain boundary enriched materials are shown in Table 2.

[0076] [Table 2]

[0077] These materials were blended with PVDF binder and conductive carbon in a slurry solvent of NMP, respectively, and coated onto an aluminum foil current collector. Cathode electrodes were then punched out from the foil and combined with an MCMB graphite anode, a porous polypropylene separator, and a carbonate-based electrolyte in a "full" coin cell format for electrochemical cycle life testing. Cathode electrodes were also combined with a lithium metal anode, a porous polypropylene separator, and a carbonate-based electrolyte in a "half" coin cell format for electrochemical discharge capacity testing.

[0078] The results of the half-cell tests are shown below in Table 3. For both samples, high discharge capacities of over 205 mAh / g at C / 20 are achieved.

[0079] [Table 3]

[0080] A series of charge / discharge cycles were repeated on these full cells, first at room temperature and then at 45°C. The results of the tests at 45°C for 100 to 200 cycles are shown in Figures 2 and 3 below. Figure 2 is a graph of the discharge capacity degradation at 45°C for 100 to 200 cycles for dual cells containing cathode materials with large crystallites or nanocrystallites. Figure 3 shows the increase in dimensionless impedance values ​​for dual cells containing cathode materials with large crystallite sizes or small crystallite sizes (e.g., nanocrystallites) corresponding to the cycle data shown in Figure 2. The impedance values ​​were measured every 20 charge / discharge cycles. Of note here is the improvement of the initial high discharge capacity and initial low impedance for the materials with small nanocrystallites. More specifically, 85% or more of the remaining capacity is achieved at 200 cycles. Furthermore, capacity retention during cycling is better and the rate of impedance increase is lower for materials with small nanocrystallites.

[0081] Example 2: Li with different crystallite sizes (0.98) Mg (0.02) Ni (0.863) Co (0.131) Al (0.006) O (2) Four cathode powders with the following formulation: Four electrochemically active, nickel-rich, polycrystalline 2D α-NaFeO2-type layered structure particles with different crystallite sizes were prepared. The four polycrystalline 2D α-NaFeO2-type layered structure samples prepared had a bulk composition of Li (0.98) Mg (0.02) Ni (0.863) Co (0.131) Al (0.006) O (2.0) had the following characteristics:

[0082] A green body blend was synthesized from two powder components substantially the same as in Example 1. The powders were combined in a 1 / 2 gallon HDPE bottle and shaken on a paint shaker for 10 minutes to thoroughly mix. The green body blend was then fired in a controlled air atmosphere, thereby minimizing water and CO2. Firing formed a sintered ceramic product, which was then processed to form a free-flowing powder.

[0083] The two powders combined with the green bodies were finely divided lithium hydroxide and mixed metal hydroxide. The lithium hydroxide was divided by shaking 250 g of the lithium hydroxide with 1200 g of yttrium stabilized zirconia (YSZ) media (spherical, 1 / 4 inch diameter) in a 1 / 2 gallon HDPE bottle for 45 minutes. The mixed metal hydroxide had a metal composition of 90 at% Ni, 8 at% Co, and 2 at% Mg. It was manufactured by the precursor supplier Hunan Brunp Recycling Technology Co. Ltd. using standard methods for preparing nickel hydroxide-based materials.

[0084] The heating curve for the first firing followed two ramps / dwells followed by natural cooling to 130°C. The first ramp / dwell was from ambient to 450°C at 5°C / min and held for 2 hours, while the second ramp / dwell was from 450°C to maximum temperature at 2°C / min and held for 6 hours. The four materials described were fired at different maximum temperatures of 640°C, 660°C, 680°C and 700°C.

[0085] For the material produced at the three lowest temperatures (i.e., 640°C, 660°C, and 680°C), a single green body blend was produced from 252 g of lithium hydroxide and 961 g of mixed metal hydroxide powder. This was then divided into three portions and each of the three portions was placed into one of three crucibles for firing. After firing, subsequent processing included first crushing the sinter cake with a mortar and pestle so that the resulting powder passed through a #35 sieve. This powder was then ball milled for 5 minutes with 2 cm drum YSZ media in a 1 gallon jar and passed through a #270 sieve.

[0086] The material calcined at 700°C included a green body blend made from 252g lithium hydroxide and 941g mixed metal hydroxide. This blend was calcined in nine crucibles spaced equally in three identically programmed furnaces. After calcination, subsequent processing included first crushing the sinter cake with a mortar and pestle so that the resulting powder passed through a #35 sieve. This powder was then ball milled for 10 minutes with 2cm drum YSZ media in a 1 gallon jar and passed through a #270 sieve.

[0087] Prior to forming the electrodes, the synthesized powders were coated with a mixture of cobalt and aluminum using the same method, sufficient to produce the aforementioned formulation. After coating both materials, the materials were subjected to another heat treatment under flowing CO2-free dry air. The heating curve used for this treatment was a ramp from 25°C to 450°C at 5°C / min with a soak time of 1 hour, followed by a second ramp to 700°C at 2°C / min and a soak time of 2 hours. The materials were then naturally cooled to 100°C and ground in a ball mill for 5 minutes.

[0088] For each of the four cathode powders, an electrode coating was prepared by combining the cathode powder with PVdF (Kureha KF-1120) and carbon (Denka black) in N-methylpyrrolidinone to form a slurry, and then coating the respective slurry onto an aluminum foil current collector. Cathodes were then punched out from the coated aluminum foil.

[0089] Half-cells were assembled by combining this cathode with lithium foil, a polyolefin separator (Celgard 2500), and an electrolyte of 1M LiPF6 in 1 / 1 / 1 (by volume) EC / DMC / EMC with 1% VC by weight (Kishida Chemical) into 2025 coin cells. The capacity of each cell was measured by calculating from the electrode mass, assuming a cathode material with a capacity of 200 mAh / g. These cells were then charged to 4.3 V at C / 20 and discharged at a rate of C / 20 - 5C. In reference to charge or discharge rate, C refers to the C rate, which is the rate at which the cell is charged and discharged in one hour. The results of the half-cell analysis are shown in Table 4.

[0090] [Table 4]

[0091] Full cells were assembled by combining the cathodes with graphite anodes, polyolefin separators (Celgard 2500) and an electrolyte of 1M LiPF6 in 1 / 1 / 1 (by volume) EC / DMC / EMC with 1% VC by weight (Kishida Chemical) in 2025 coin cells, half of which had an aluminum-coated cathode. The capacity of each cell was measured, calculated from the electrode mass, assuming a cathode material with a capacity of 200 mAh / g. The anodes were matched to the cathode mass such that the anode capacity exceeded the cathode by a factor of 1.27 to 1.30.

[0092] Graphite anode coatings with MCMB 1028 active material were prepared by blending the active material with PVdF (Kureha KF-1120) and carbon (Denka black) in N-methylpyrrolidinone to form slurries, and then coating each slurry onto a copper foil current collector. Anodes were then punched from the coated copper foil.

[0093] A full coin cell was then formed at C / 5 at 25° C. and cycled with a charge current of 1.5 C to 4.25 V and a discharge current of 1 C terminating at 2.7 V at 45° C. After every 20 cycles, the cell was charged at a 1 C rate to 4.2 V (CCCV) and the cell was discharged to 2.7 V to characterize the capacity and impedance. The time spent at constant voltage during this characterization step (i.e., the CV step) was used as a measure of the impedance.

[0094] [Table 5]

[0095] Crystallite size was determined using powder X-ray diffraction patterns collected by continuous scanning from 2θ = 12° to 120° at 0.75° / min using an automated Shimadzu XRD-6000 diffractometer equipped with a Cu X-ray tube. Atomic structure and crystallite size analysis were performed using Rietveld techniques implemented in the MDI Jade 7 program. The procedure for atomic structure refinement will be apparent to one skilled in the art. Such refinement was used to determine the a- and c-lattice parameters of the LiNiO2R-3m layered crystal structure and the Ni occupying the Li sites. 2+The relative amounts of ions and the relative z-positions of oxygen atoms were obtained. A third order polynomial background curve and a Pseudo-Voigt profile shape function were used for peak fitting. Peak broadening was only fitted in the crystallite size case (undistorted). An instrumented FWHM calibration curve was obtained by profile fitting diffraction patterns of a NIST 640c Si calibration standard. The undistorted crystallite size fitting is used to measure the average primary crystallite size of materials synthesized under different reaction conditions. The results are shown in Table 6.

[0096] [Table 6]

[0097] After applying the coating and briefly re-firing the materials, some crystal growth is observed by XRD for most of the materials. At 700°C firing, an apparently small reduction in crystallite size is observed as a result of slight lattice parameter distortion caused by grain boundary enrichment. However, the same continuous orientation of the crystallites produced by the first firing is maintained. Also, the disorder is not evident, as the Ni 2+ The value is kept low at less than 3.5 at% Ni.

[0098] [Table 7]

[0099] Reference is now made to FIG. 4, which is a graph showing impedance values ​​at 100-200 cycles for two samples each of the four cathode powders, where it is shown that the first firing was performed at a temperature of 700° C. or less. As shown, the crystallite size decreases as the maximum firing temperature decreases. Furthermore, the impedance slope, quantified in Table 5, also decreases with firing temperature, although the impedance slope increases with firing at 640° C. As shown in Table 4, low impedance increase rates and high discharge capacities during battery charge / discharge cycling are achieved by using maximum firing temperatures below 700° C. and above 640° C.

[0100] It should now be appreciated that the embodiments described herein can be directed to compositions and methods of making positive electrode (cathode) active materials for Li-ion batteries having small nanocrystals to reduce the rate of impedance increase during charge / discharge cycling of the battery. The compositions and methods of making described achieve materials with average crystallite sizes of 85 nm or less (or 105 nm or less for grain boundary enriched particles) in high nickel formulations, including active polycrystalline particles forming positive electrodes that also have high discharge capacities of 205 mAh / g or more at C / 20. The provided compositions and methods of making positive electrode (cathode) active materials exhibit significant improvements in electrochemical performance and stability, whereby lithium is deintercalated and reintercalated into the crystal lattice.

[0101] List of Exemplary Embodiments 1. Electrochemically active polycrystalline particles comprising: The nanocrystals include a plurality of nanocrystals, the plurality of nanocrystals being Li 1+x MO 2+y (In the formula, -0.1≦x≦0.3, -0.3≦y≦0.3, and M has a first composition defined by: The electrochemically active polycrystalline particles, wherein said plurality of nanocrystals has an average crystallite size of less than or equal to 85 nanometers as measured by x-ray diffraction. 2. The particle of embodiment 1, wherein said size of said plurality of nanocrystals has an average crystallite size of greater than or equal to 50 nanometers and less than or equal to 85 nanometers. 3. The particle of embodiment 1, wherein said crystallite size of said plurality of nanocrystals is less than or equal to 80 nanometers. 4. The particle of embodiment 1, wherein said size of said plurality of nanocrystals is 70 nanometers or less. 5. The particle of embodiment 1, wherein the size of the plurality of nanocrystals is between 55 nanometers and 70 nanometers. 6. The particle of any one of the preceding embodiments, wherein M further comprises one or more elements selected from the group consisting of Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Zr, Y, Cr, Mo, Fe, V, Si, Ga, and B. 7. The particle of any one of the preceding embodiments, further comprising grain boundaries between adjacent grains of the plurality of nanocrystals and having a second composition, optionally having an α-NaFeO2-type layered structure, a cubic structure, or a combination thereof, wherein a concentration of cobalt at the grain boundaries is greater than a concentration of cobalt in the nanocrystals. 8. The particle of any one of the preceding embodiments, wherein M comprises an atomic percent of nickel of 75% or more, optionally 80% or more, optionally 85% or more. 9. The particle of any one of the preceding embodiments, wherein M comprises nickel in an atomic percent of 90% or more, optionally 95% or more. 10. Further comprising an outer coating on a surface of the aforementioned particle, the outer coating comprising: Oxides of one or more elements selected from Al, Zr, Y, Co, Ni, and Li; Fluorides containing one or more elements selected from Al, Zr, and Li; A carbonate containing one or more elements selected from Al, Co, and Li; or Phosphate containing one or more elements selected from Al and Li 10. The particle of any one of the preceding embodiments, comprising: 11. The particle of any one of the preceding embodiments, wherein M comprises an atomic percent of nickel of 85% or more, optionally 95% or more, and wherein the size of the plurality of nanocrystals has an average size of 50 nanometers or more and 85 nanometers or less. 12. The particle of any one of aspects 7 to 11, wherein the average size of the nanocrystals is 105 nanometers or less. 13. The particle of embodiment 7 or 10, wherein the average size of said nanocrystals is less than or equal to 105 nanometers. 14. The particle of any one of aspects 7, 10, 8 or 9, wherein the average size of the nanocrystals is 105 nanometers or less. 15. A method for producing an electrochemically active particle, optionally according to any one of embodiments 1 to 14, comprising: providing a first mixture comprising lithium hydroxide or a hydrate thereof and a precursor hydroxide or carbonate comprising nickel; calcining said first mixture to a maximum temperature of less than 700° C. to form a first material comprising a plurality of nanocrystals having a size of 85 nanometers or less. The method includes: 16. The method of claim 15, wherein the maximum temperature is 680° C. or less. 17. The method of claim 15, wherein the maximum temperature is 660° C. or less. 18. The step of calcining the first mixture further comprises: Ramp the temperature from about 25° C. to about 450° C. at about 5° C. / min; soaking at the aforementioned temperature of about 450°C for about 2 hours; increasing said temperature from about 450°C to a maximum temperature of about 650°C to about 699°C; and Heat soak at the aforementioned maximum temperature of about 650℃ to about 699℃ for about 6 hours. 20. The method of embodiment 15, comprising: 19. The method of claim 15, wherein the maximum temperature is about 660°C to about 680°C. 18. Combining the first material with a second material comprising at least one of cobalt, aluminum, or a combination thereof to form a second mixture; and heat treating said second mixture to a second maximum temperature of 725° C. or less to produce particles further comprising grain boundaries between adjacent nanocrystals and having a second composition, optionally having an α-NaFeO2-type layered structure, a cubic structure, or a combination thereof, wherein a concentration of cobalt in said grain boundaries is greater than a concentration of cobalt in said nanocrystals; and wherein said plurality of nanocrystals have a size of 105 nanometers or less. 20. The method of any one of embodiments 15 to 19, further comprising: 20. The method of claim 19, wherein the second maximum temperature is 700° C. or less. 21. The method of any one of aspects 15 to 20, wherein the particles comprise an atomic percent of nickel of 75% or more, optionally 80% or more, optionally 85% or more. 22. The method of any one of aspects 15 to 20, wherein the particles comprise nickel in an atomic percent of 90% or more, optionally 95% or more. 23. The method of any one of aspects 15 to 22, wherein the average size of the plurality of nanocrystals is greater than or equal to 50 nanometers and less than or equal to 85 nanometers. 24. The method of any one of aspects 15 to 22, wherein the size of the plurality of nanocrystals is 80 nanometers or less. 25. The method of any one of aspects 15 to 22, wherein the size of the plurality of nanocrystals is 70 nanometers or less. 26. The method of any one of aspects 15 to 22, wherein the size of the plurality of nanocrystals is 66 nanometers or less. 27. The method of any one of embodiments 15 to 22, wherein the size of the plurality of nanocrystals is between 50 nanometers and 80 nanometers, optionally between 55 nanometers and 70 nanometers. 28. The method of embodiment 18, wherein said plurality of nanocrystals have a size of 100 nanometers or less, optionally 95 nanometers, optionally 90 nanometers, optionally 85 nanometers, optionally 80 nanometers, optionally 75 nanometers, optionally 70 nanometers. 29. The method of claim 28, wherein the second maximum temperature is 700° C. or less. 30. The method of embodiment 28 or 29, wherein the particles comprise an atomic percent of nickel of 75% or more, optionally 80% or more, optionally 85% or more. 31. The method of embodiment 28 or 29, wherein the particles comprise an atomic percent of nickel of 90% or more, optionally 95% or more. 32. Electrochemically active polycrystalline secondary particles comprising: Li 1+x MO 2+y (In the formula, -0.0≦x≦0.3, -0.3≦y≦0.3, and M has a first composition defined by: M comprising at least 80 atomic percent nickel; a plurality of nanocrystals having a size of 105 nanometers or less as measured by x-ray diffraction; and grain boundaries between adjacent nanocrystals of the plurality of nanocrystals and having a second composition, optionally having an α-NaFeO2-type layered structure, a cubic structure, or a combination thereof, wherein a concentration of cobalt at the grain boundaries is greater than a concentration of cobalt in the nanocrystals. 33. The concentration of cobalt in the nanocrystal is between about 0.25 atomic percent and about 17 atomic percent; 33. The particle of embodiment 32, wherein a concentration of cobalt at said grain boundary is from about 0.5 atomic percent to about 32 atomic percent, each based on the total atomic composition of said particle. 34. The particle of embodiment 32, wherein M further comprises one or more elements selected from the group consisting of Al, Mg, Co, Mn, Ca, Sr, B, Zn, Ti, Zr, Y, Cr, Mo, Fe, V, Si, Ga and B, and wherein said one or more elements are present in the Li layer, the M layer, or both layers of said nanocrystal. 35. The particle of any one of aspects 32 to 34, wherein the size of the plurality of nanocrystals is 100 nanometers or less. 36. The particle of any one of embodiments 32 to 34, wherein the size of the plurality of nanocrystals is between 70 nanometers and 100 nanometers, optionally between 75 nanometers and 90 nanometers. 37. The particle of any one of embodiments 32 to 36, wherein M comprises an atomic percent of nickel of 75% or more, optionally 80% or more, optionally 85% or more. 38. The particle of any one of embodiments 32 to 36, wherein M comprises nickel in an atomic percent of 90% or more, optionally 95% or more. 39. An electrochemical cell comprising a cathode active material comprising particles according to any one of embodiments 1 to 14 or 32 to 37. 40. A cathode comprising a cathode active material comprising the particles of embodiment 1 or 26.

[0102] Various modifications other than those shown and described herein will be apparent to those skilled in the art in view of the above description, and such modifications are intended to be included within the scope of the present disclosure.

[0103] It is understood that all reagents are obtained from sources known in the art unless otherwise specified.

[0104] The patents, publications, and applications mentioned in this specification are indicative of the level of those skilled in the art to which this disclosure pertains, and are hereby incorporated by reference to the same extent as if each individual patent, publication, or application was specifically and individually incorporated by reference herein.

[0105] The foregoing description describes certain embodiments of the present invention, but is not intended to limit its practice. The following claims, including all equivalents thereof, are intended to define the scope of the present invention.

Claims

1. Electrochemically active polycrystalline particles comprising: a plurality of nanocrystals, the plurality of nanocrystals being Li 1+x M.O. 2+y (In the formula, −0.1≦x≦0.3, −0.3≦y≦0.3, and M has a first composition defined by: M comprises 75 atomic percent or more of nickel, and M further comprises 3.5 at.% or less of Ni 2+ at the Li sites of the crystal structure; and the plurality of nanocrystals having an average crystallite size of at least 50 nanometers and not more than 85 nanometers as measured by X-ray diffraction; and between adjacent nanocrystals of the plurality of nanocrystals, and 2 The electrochemically active polycrystalline particles further comprise grain boundaries having a second composition having a layered type structure, a cubic structure, or a combination thereof, wherein a concentration of cobalt in the grain boundaries is greater than a concentration of cobalt in the nanocrystals.

2. 2. The particle of claim 1, wherein M comprises one or more elements selected from the group consisting of Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Zr, Y, Cr, Mo, Fe, V, Si, Ga, and B.

3. The particle further comprises an outer coating on a surface thereof, the outer coating comprising: Oxides of one or more elements selected from Al, Zr, and Li; Fluorides containing one or more elements selected from Al, Zr, and Li; Li-containing carbonate; or Phosphate containing one or more elements selected from Al and Li The particle of claim 1 or 2, comprising:

4. 1. A method of making electrochemically active particles comprising: providing a first mixture comprising lithium hydroxide or a hydrate thereof and a precursor hydroxide comprising nickel; calcining the first mixture to a maximum temperature of less than or equal to 680° C. to form a first material comprising a plurality of nanocrystals having a size of greater than or equal to 50 nanometers and less than or equal to 85 nanometers as measured by x-ray diffraction; combining the first material with a second material comprising at least one of cobalt, or a combination of cobalt and aluminum to form a second mixture; and The second mixture is heat treated to a second maximum temperature of 725° C. or less to form nanocrystals between adjacent nanocrystals and α-NaFeO 2 producing particles further comprising grain boundaries having a second composition having a layered type structure, a cubic structure, or a combination thereof, wherein a concentration of cobalt in the grain boundaries is greater than a concentration of cobalt in the nanocrystals, and the plurality of nanocrystals have a size between 60 nanometers and 105 nanometers inclusive; The nanocrystals are Li 1+x M.O. 2+y (In the formula, −0.1≦x≦0.3, −0.3≦y≦0.3, and M comprises 75 atomic percent or more of nickel; The method includes:

5. The step of calcining the first mixture further comprises: Ramp the temperature from 25° C. to 450° C. at 5° C. / min; soaking at said temperature of 450° C. for 2 hours; increasing the temperature from 450° C. to the maximum temperature; and Soak at the maximum temperature for 6 hours. The method of claim 4 , comprising:

6. The method of claim 4 or 5, wherein the particles comprise nickel at an atomic percent of 80% or greater.

7. Electrochemically active polycrystalline secondary particles comprising: A plurality of nanocrystals, 1+x M.O. 2+y (In the formula, −0.0≦x≦0.3, −0.3≦y≦0.3, and M comprises 10 atomic percent or more of Nickel of M, and M further comprises 3.5 at.% or less of Ni2+ at the Li sites of the crystal structure, wherein M comprises one or more elements selected from the group consisting of Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Zr, Y, Cr, Mo, Fe, V, Si, Ga, and B, wherein the one or more elements are present in the Li layer, the M layer, or both layers of the nanocrystal; the plurality of nanocrystals having a size of at least 50 nanometers and not more than 85 nanometers as measured by x-ray diffraction; between adjacent nanocrystals of the plurality of nanocrystals, and 2 and grain boundaries having a second composition having a layered type structure, a cubic structure, or a combination thereof, wherein a concentration of cobalt in the grain boundaries is greater than a concentration of cobalt in the nanocrystals.

8. The particle further comprises an outer coating on a surface thereof, the outer coating comprising: Oxides of one or more elements selected from Al, Zr, and Li; Fluorides containing one or more elements selected from Al, Zr, and Li; Li-containing carbonate; or Phosphate containing one or more elements selected from Al and Li The particle of claim 1 or 2, comprising:

9. 10. An electrochemical cell comprising a cathode active material comprising the particles of claims 1, 2, 7 or 8.

10. A cathode comprising a cathode active material comprising the particles of claims 1, 2, 7 or 8.

Citation Information

Patent Citations

  • Polycrystalline metal oxide, method for producing the same, and product containing the same

    JP2014528891A

  • JPP7412080B